The Use of Discovery Learning Model to Improve Problem Solving Ability of Students' Mathematical - Ani Latifah; Reni Dwi Puspitasari; Zulaiha Zulaiha (CV. Tripe Konsultan, 2023)
Utilization of various learning models at SMP Negeri 20 Bandar Lampung is not optimal. Yet, teachers only use conventional learning models to teach various learning materials and are more active during learning than students. This causes low students' mathematical problem-solving abilities in learning mathematics, so students get a low value. The study aimed to determine whether the mathematical problem-solving abilities of students who used the discovery learning model were better than those whose learning used conventional models in class VII students of SMP Negeri 20 Bandar Lampung. This research is a quasi-experimental design study with two groups. The data collection technique used is a test of mathematical problem-solving ability. The analysis technique in this study is a statistical technique through the t-test. The results of this study indicate that students using the discovery learning model are better than students whose learning uses conventional models on students' mathematical problem-solving abilities.